Angle-specific eccentric hamstring fatigue after simulated soccer - Cohen, D. D.; Zhao, B.; Okwera, B.; Matthews, M. J.; Delextrat, A. (International Journal of Sports Physiology and Performance, 2015)
Purpose: To evaluate the effect of simulated soccer on the hamstrings eccentric torque-angle profile and angle of peak torque (APTeccH), and on the hamstrings:quadriceps torque ratio at specific joint angles (ASHecc:Qcon). Methods: The authors assessed dominant-limb isokinetic concentric and eccentric knee flexion and concentric knee extension at 120°/s in 9 semiprofessional male soccer players immediately before and after they completed the Loughborough Intermittent Shuttle Test (LIST). Results: The LIST resulted in significant decreases in eccentric hamstrings torque at 60°, 50°, and 10° and a significant (21.8%) decrease in ASHecc:Qcon at 10° (P < .05). APTeccH increased from 7.1° ± 1.0° to 18.8° ± 4.2° (P < .05). Eccentric hamstrings peak torque significantly declined from 185.1 ± 70.4 N·m pre-LIST to 150.9 ± 58.5 N·m post-LIST (P = .002), but there were no significant changes in hamstrings or quadriceps concentric peak torque (P = .312, .169, respectively). Conclusions: Simulated soccer results in a selective loss of eccentric hamstrings torque and hamstrings-to-quadriceps muscle balance at an extended joint position and a shift in the eccentric hamstrings APT to a shorter length, changes that could increase vulnerability to hamstrings injury. These findings suggest that injury-risk screening could be improved by evaluating the eccentric hamstrings torque-angle profile and hamstrings strength-endurance and that the development of hamstrings fatigue resistance and long-length eccentric strength may reduce injury incidence.